Chitosan-containing gum chewing accelerates antibacterial effect with an increase in salivary secretion - Hayashi, Y.; Ohara, N.; Ganno, T.; Ishizaki, H.; Yanagiguchi, K. (Journal of dentistry, 2007)
This study was designed to confirm the mechanical efficacy of chewing chitosan-containing gum to suppress the growth of oral bacteria compared to a mouth rinse, and to demonstrate the increased salivary secretion due to chewing chitosan-containing gum. Twelve healthy subjects were recruited from among the staff and students of Nagasaki University School of Dentistry. For the slab of gum study, the subjects chewed chitosan-containing gum for 5 min and then rested for 5 min. For the testing of the chitosan mouth rinse solution, the subjects gargled 10 mL of solution for 30 s followed by resting for 9 min 30 s. These protocols were continuously repeated five times for 50 min on the same day. For the salivary secretion experiment, the gum chewing was repeated three times per day for 2 days. The amount of oral bacteria in the subjects who chewed chitosan-containing gum significantly decreased during all three sampling times except at 60 min for total bacteria in comparison to those in the rinse group. Chitosan-containing gum chewing also significantly increased the secretion of saliva. Chitosan-containing gum chewing has a greater antibacterial effect and it also increases salivary secretion. The present findings strongly indicate that the application of natural materials such as chitosan is useful for both oral health and the quality of life.